Acute phase response in experimentally infected broilers with avian infectious bronchitis virus serotype 4/91 - SEIFI, S.; ALIAN SAMAKKHAH, S. H.; ABSALAN FARD, K. (Journal of the Hellenic Veterinary Medical Society, 2017)
Measurement of acute phase proteins is important for diagnosis of animal diseases. In the present study, effects of avian infectious bronchitis virus infection on acute phase response and acute phase proteins were determined. Thirty one-day-old commercial broiler chicks were reared in experimental facilities and, at the age of 21 days, were challenged intranasally with 0.2 mL of allantoic fluid virus suspension (titre 106.5 EID50 per 0.1 mL). Serum samples were obtained prior to challenge and on days 1, 2, and 5 post-inoculation. Haptoglobin, serum amyloid A and C- reactive protein concentrations were measured. Our results showed that all investigated acute phase proteins increased significantly after infection, with mean maximum concentrations between 24 h and 48 h. No correlation was observed between plasma acute phase proteins in the chickens prior and post inoculation of the virus. Haptoglobin was most sensitive factor to change in the exposed birds.